Glycemic control and cardiovascular outcomes in patients with diabetes and coronary artery disease according to triglyceride-glucose index: a large-scale cohort study - Zhangyu Lin; Jining He; Sheng Yuan; Chenxi Song; Xiaohui Bian; Min Yang; Kefei Dou (Cardiovascular Diabetology, 2024)
Abstract Background The role of triglyceride-glucose (TyG) index, an insulin resistance indicator, in glycemic management for diabetic patients with coronary artery disease (CAD) was still unknown. Therefore, we aimed to explore the association between glycemic control and cardiovascular (CV) outcomes in patients with diabetes and CAD according to different TyG index levels. Methods A total of 9996 diabetic patients with angiograph-proven CAD were consecutively recruited from 2017 to 2018 at Fuwai Hospital. Patients were assigned into 3 groups according to TyG index tertiles (T) (T1: <8.895; T2: 8.895-9.400; T3: ≥9.400). According to American Diabetes Association guidelines, controlled glycemia was defined as targeting glycosylated hemoglobin Alc (HbA1c) < 7%. The primary endpoint was CV events including CV death, nonfatal myocardial infarction, and nonfatal stroke. Results During a median 3-year follow-up, 381 (3.8%) CV events occurred. Overall, high TyG index (T3) was associated with increased risk of CV events (hazard ratio [HR]: 1.40; 95% confidence interval [CI]: 1.02–1.94) compared with the lowest TyG index (T1) after multivariable adjustment. Upon stratification by the TyG index, in fully adjusted models, controlled glycemia was associated with reduced risk of CV events in the high TyG index (T3) subgroup (HR: 0.64; 95%CI: 0.42–0.96) but not in the low (T1; HR: 0.79; 95%CI: 0.53–1.16) and moderate (T2; HR: 0.84; 95%CI: 0.56–1.25) TyG index subgroups. Conclusions Controlled glycemia was associated with improved CV outcomes in patients with diabetes and established CAD, especially in those with high TyG index levels. Our study, for the first time, provided valuable information that TyG index could help making risk stratification on the glycemic management in diabetic patients with CAD.